EVALUASI PELAKSANAAN INSPEKSI APD DI H2, CO2 DAN DRY ICE PLANT DI PT. X KAWASAN GRESIK - Cynintya Rahmi Chairunnisa; Tjipto Suwandi (The Indonesian Journal of Occupational Safety and Health, 2017)
Hazards are potentially harmful. In the gas industry that has raw materials, tools / machinery, production and hazardous environment must use the completely and correctly. The purpose of this study is to evaluate the implementation of safety inspection and compliance with the use of PPE in H2, CO2 and dry ice plant in PT. X Region Gresik.This research is descriptive observational research, using cross sectional research design. The sample was 6 workers as sample interview and observation and 1 (one) HSE officer as sample of interview. The data collection includes safety inspection and the compliance of plant workers in the use of PPE. The data analysis used in this research is presented in tabular and narrative form, then using cross tabulation to see whether there is a correlation between the conformity of the number of PPE, the condition of PPE to the worker compliance in the use of PPE.The results showed that majority workers did not use PPE, the number of is not suitable with the number of workers, the condition of PPE is not feasible and compliance of the use of PPE plant workers is still low. Significant linkage between the availability of PPE TO compliance with the use of and the lack of significant correlation between the condition of PPE to the compliance of usage.The conclusion of this research is low frequency of safety inspection. Should increase frequency of safety inspection. And also HSE officer officer in carrying out safety inspection. The suggestion is to increase the compliance of workers in the use of PPE. Keywords: Safety inspection , PPE.